A Critical consideration of the use of trauma as an approach to understanding Korean cinema. - Ha, Ju-Yong; David, Joel (2014)
A number of reasons have been forwarded to explain the emergence and current dominance of the Korean Wave in film, as well as the larger phenomenon of Hallyu, the term by which the popular-culture Korean wave has been known. Most of these accounts for the New
Korean Cinema, the filmic equivalent of the Korean Wave, are tied to attempts to understand other national cinemas in Asia in terms of their respective countries’ encounters with modernization. This paper attempts to (1) provide a historically grounded perspective on why and how film is currently being used in Korea to recapture and revaluate traumatic experiences on the part of both filmmakers and audiences, and (2) to suggest ways in which these uses of trauma may be shifting or eroding.
Keywords: Korean Cinema; Trauma